2017
DOI: 10.1098/rspa.2017.0358
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the hypothetical sky-polarimetric Viking navigation versus sky conditions: revealing solar elevations and cloudinesses favourable for this navigation method

Abstract: Changes performed along the comments of Referee 1 are marked by violet.Changes performed along the comments of Referee 2 are marked by green.Sky conditions favourable for Viking navigation RSPA-2017-0358-R2 Száz et al. 2 AbstractAccording to Thorkild Ramskou's theory proposed in 1967, under overcast and foggy skies Viking seafarers might have used skylight polarization analyzed with special crystals called sunstones to determine the position of the invisible Sun. After finding the occluded Sun with sunston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…The effect of consistent overestimations/underestimations of the deduced solar elevation was measured by Száz et al . [ 20 ] and was included in the computation of the θ−ρ matrix of the north uncertainties [ 21 ]. — Further simulations could also answer the question: How robust are the very high navigation success rates obtained, with respect to altering various parameters and environmental/meteorological conditions?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of consistent overestimations/underestimations of the deduced solar elevation was measured by Száz et al . [ 20 ] and was included in the computation of the θ−ρ matrix of the north uncertainties [ 21 ]. — Further simulations could also answer the question: How robust are the very high navigation success rates obtained, with respect to altering various parameters and environmental/meteorological conditions?…”
Section: Discussionmentioning
confidence: 99%
“…The effect of consistent overestimations/underestimations of the deduced solar elevation was measured by Száz et al . [ 20 ] and was included in the computation of the θ−ρ matrix of the north uncertainties [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the Vikings possibly used the polarization patterns of skylight for solving challenging navigation tasks, such as sailing to Greenland from Norway. The authors determined the accuracy [22] of hypothetical sky-polarimetric Viking navigation for 1080 different sky conditions that were characterized by parameters such as solar elevation and cloudiness [23]. A simulation based on a large amount of actual data [23], obtained using imaging polarimetry, shows that Viking sailors could have travelled to Greenland from Norway using polarization information [24].…”
Section: Introductionmentioning
confidence: 99%